Konsep Pendidikan Ki Hajar Dewantara: Sinergitas Guru, Orang Tua, dan Pemuda dalam Menghadapi Tantangan Pendidikan di Masa Pandemi - Nur Fajriati Nadlifatil K; Qinthara Rafiandra (Program Studi Pendidikan Profesi Guru, Universitas Sarjanawiyata Tamansiswa Yogyakarta, Indonesia., 2022)
Online Learning (PJJ) causes students to spend more time studying at home. Teachers are required to adjust learning during the pandemic while ensuring that educational goals can still be achieved. However, during the pandemic, teachers have limitations in carrying out their duties as educators. Ki Hajar Dewantara has formulated a comprehensive education concept that involves the synergy of teachers, parents, and youth in an effort to achieve educational goals. Educational achievements do not only talk about cognitive aspects, but also other aspects which are termed cipta, rasa, and karsa. This research is a literature study sourced from the journals, books, and writings of Ki Hajar Dewantara. Ki Hajar Dewantara's educational concept emphasized that education is not only the responsibility of teachers, but also family and community members (youth organizations) known as the Education Tricenter. Meanwhile, teachers are still equipped with the ability to become professional teachers whose duties are not only to teach, but also to educate in accordance with the educational values ​​that have been initiated by Ki Hajar Dewantara.